Dietary glycemia as a determinant of health and longevity. (December 2015) - Whitcomb, Elizabeth A.; Chiu, Chung-Jung; Taylor, Allen
Abstract: The role of diet in extending lifespan and healthspan has been the subject of much research and debate. Our recent epidemiological and in vivo data suggest that carbohydrate quality can be a major determinant in prolonging eye health. Additionally, excessive carbohydrate intake can contribute to the exacerbation of many different diseases. The metabolic diversity of the tissues that are affected by excessive carbohydrate intake suggests that dietary carbohydrate quality may affect cellular homeostasis.